Conversational management of network trouble perturbations in personal videoconferencing - Rintel, Sean (CHI 2010, 2010)
Domestic personal videoconferencing (PV) is vulnerable to network trouble perturbations. This paper shows that long-distance couples treat perturbations as a matter of social management as much as technological resolution. Three management strategies are illustrated: technology-oriented remedies, content-oriented remedies, and non-remedial accounts for trouble. All three involve collaborative work to account for the effect of technology on conversational continuity and the relationship.